Pengaruh Intellectual Capital, Perubahan Cash Flow, dan Liquidity Terhadap Value of the Firm dengan Corporate Social Responsibility sebagai Variabel Moderating - Ekadjaja, Margarita; Ekadjaja, Agustin (Manajemen Bisnis Kompetensi, 2018)
In this modern era, awareness that to increase competitiveness is not only depend on owned tangible resource, intangible resource strength such as Intellectual Capital. cash flowand availability of fund (liquidity) of a firm is also important to sustain it’s life. Those are considered as one of the important component of financial report that would be considered by both domestic investors and foreign investors. Nowadays a firm is also expected to take responsibility to the society both socially and naturally, also known as Corporate Social Responsibility (CSR).Purpose of this research is to understand the impact of intellectual capital, cash flow changes, liquidity, and CSR as moderating variabel against value of the firm, as a model to control conflict of agency. This research is taking manufacturing industry which are registered in Indonesian stock exchange in year 2014-2015 as population. By using purposive sampling technique.Research result based on testing of those three independent variables (intellectual capital, cash flow changes, and liquidity) and moderation variable (CSR) which done simultaneously in year 2014-2015 shows there is a significant impact and moderating the relation between independent variable and dependent variables, therefore, intellectual capital, cash flow changes, liquidity and CSR can be used as consideration for the investors in taking investment decision.Keywords: Intellectual capital, cash flow, liquidity, Corporate Social Responsibility, value of the firm